Qualiquantitatve study of biogas produced by substrates in batch biodigestors - Galbiatti, João A. [UNESP]; Caramelo, Anaira D. [UNESP]; Silva, Flavia G. [UNESP]; Gerardi, Eliana A.B. [UNESP]; Chiconato, Denise A. (FapUNIFESP (SciELO), 2010)
Aiming to study the biogas produced by 5 substrates from both quality and quantity point of view, this research was conducted at the Rural Engineering Department of FCAV/UNESP - Brazil, State of São Paulo. The substractes that were used in the anaerobic digestion were characterized as: 1 - Slaughter fowls' manure with napier grass bed (MFNG); 2 - Slaughter fowls' manure with triturate napier grass bed (MFNGT); 3 - Suine manure (SM); 4 - Bovine manure (BM) and 5 - Bovine manure mixed with 50% of sugarcane bagasse (BM50S). From the data colIected it was concluded that: the substract (MFNG) and the substract containing SM produced higher and lower volumes of biogas respectively, when compared to the others; the mixture of sugarcane bagasse in the substract containing Bovine manure damages the accumulated biogas production and its quality; 57 days after filling the biodigestors, alI substrates produced biogas with a methane leveI higher than 48% except for the substrates containing Suine manure; the triturate substrates (MFNGT) did not present such distinct characteristics from the nontriturate substrates (MFNG); the quality of biogas at the maximum production stage was similar, for alI the studied substrates; the biogas which presented higher quantity of methane in its composition was the one produced with BM, overcoming the value up to 17.7% over the MFNGT production.
Estudo qualiquantitativo do biogás produzido por substratos em biodigestores tipo batelada
Keywords: Energy; Manure; Methane; Quality